The large conductance Ca2+ -activated K+ (BKCa) channel regulates cell proliferation in SH-SY5Y neuroblastoma cells by activating the staurosporine-sensitive protein kinases - Curci, Angela; Mele, Antonietta; Camerino, Giulia Maria; Dinardo, Maria Maddalena; Tricarico, Domenico (Frontiers in Physiology, 2014)
Here we investigated on the role of the calcium activated K+-channels(BKCa) on the regulation of the neuronal viability. Recordings of the K+-channel current were performed using patch-clamp technique in human neuroblastoma cells (SH-SY5Y) in parallel with measurements of the cell viability in the absence or presence of the BKCa channel blockers iberiotoxin(IbTX) and tetraethylammonium (TEA) and the BKCa channel opener NS1619. Protein kinase C/A (PKC, PKA) activities in the cell lysate were investigated in the presence/absence of drugs. The whole-cell K+-current showed a slope conductance calculated at negative membrane potentials of 126.3 pS and 1.717 nS(n = 46) following depolarization. The intercept of the I/V curve was -33 mV. IbTX(10-8-4x10-7M) reduced the K+-current at +30 mV with an IC50 of 1.85x10-7M and an Imax of -46%(slope=2.198)(n =21). NS1619(10-100x10-6M) enhanced the K+-current of +141%(n =6), at -10 mV(Vm). TEA(10-5-10-3M) reduced the K+-current with an IC50 of 3.54x10-5M and an Imax of -90%(slope=0.95)(n =5). A concentration-dependent increase of cell proliferation was observed with TEA showing a maximal proliferative effect(MPE) of +38% (10-4M). IbTX showed an MPE of +42% at 10-8M concentration, reducing it at higher concentrations. The MPE of the NS1619(100x10-6M) was +42%. The PKC inhibitor staurosporine (0.2-2x10-6M) antagonized the proliferative actions of IbTX and TEA. IbTX (10x10-9M), TEA (100x10-6M) and the NS1619 significantly enhanced the PKC and PKA activities in the cell lysate with respect to the controls. These results suggest that BKCa channel regulates proliferation of the SH-SY5Y cells through PKC and PKA protein kinases.